Sounds of learning: Soundscapes - teacher perceptions of acoustic environments in Finland's open plan classrooms - Hytönen-Ng Elina; Pihlainen Kaisa; Ng Kwok; Kärnä Eija (Australia's Institutes for Educational Research in New South Wales, South Australia and Western Australia, 2022)
The construction of new schools has undergone much debate as children and teachers spend a significant proportion of their lives in physical learning environments in schools. The school soundscape is central but often underestimated. In this study, we investigated teachers' experiences of soundscapes in two modern Finnish comprehensive schools by interviewing teachers (N=10). In addition, we analysed the data by the constant comparative method. According to the results, the school architecture influenced the soundscape and organisation of teaching. The designs of the schools encouraged collaborative learning through open plan learning spaces and flexible classrooms. Yet, the open plan learning environment and its soundscape did not always support the instructional needs of all children. We conclude that soundscape design should consider both the learning needs of children, and the well-being of both children and teachers.